Case Grammar in the Movie â€œThe Gentlemenâ€ Based on the Perspective of Charles J. Fillmore - Basid, Abdul; Maghfiroh, Devi Laila (Universitas Negeri Semarang, 2021)
This research aims to identify the proposition in the movie